Some considerations of choriocarcinoma in the General Hospital of Arequipa - Chávez Espinoza, Fermín (2015)
Five cases of choriocarcinoma and 101 of hydatidiform mole occurred between 1961 and 1964; this means a high incidence of chorionic tumors comparable to that registered in Hong Kong, Philippines, and Japan. AII the five cases had surgical treatment and one case received also 6-mercaptopurine. A commentary about the etiology, immunology, age and obstetrical history of the patients are made.